2015
DOI: 10.1200/jco.2014.57.2388
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Trial Evaluating the Addition of Bevacizumab to Endocrine Therapy As First-Line Treatment for Advanced Breast Cancer: The Letrozole/Fulvestrant and Avastin (LEA) Study

Abstract: The addition of bevacizumab to ET in first-line treatment failed to produce a statistically significant increase in PFS or OS in women with HER2-negative/hormone receptor-positive advanced breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(84 citation statements)
references
References 23 publications
2
81
0
1
Order By: Relevance
“…A recent meta-analysis showed that exemestane and everolimus in combination was more efficacious than fulvestrant alone in patients with relapsed BC previously treated with nonsteroidal AIs [63] . Unfortunately, in women with ER+ BC, the addition of an anti-vascular endothelial growth factor (bevacizumab) to fulvestrant or letrozole did not change the resistance of the tumor to ET, and failed to improve PFS or OS [64] .…”
Section: Endocrine Therapy and Molecular-target Therapymentioning
confidence: 99%
“…A recent meta-analysis showed that exemestane and everolimus in combination was more efficacious than fulvestrant alone in patients with relapsed BC previously treated with nonsteroidal AIs [63] . Unfortunately, in women with ER+ BC, the addition of an anti-vascular endothelial growth factor (bevacizumab) to fulvestrant or letrozole did not change the resistance of the tumor to ET, and failed to improve PFS or OS [64] .…”
Section: Endocrine Therapy and Molecular-target Therapymentioning
confidence: 99%
“…This trial has many differences compared to the LEA trial (21). In the LEA trial, patients with advanced disease were endocrine treatment-naïve.…”
Section: Patients (N=65)mentioning
confidence: 99%
“…It is used in metastatic breast cancer in biologically non-aggressive forms of the disease and in more aggressive forms after a maximal chemotherapy response has been achieved (5). For the firstline therapy of advanced breast cancer, an aromatase inhibitor combined with bevacizumab was investigated in a phase III LEA trial (21). Similarly, as reported in chemotherapy trials, the endocrine therapy-bevacizumab combination resulted in higher response rates but failed to demonstrate statistically significant improvements in both PFS and OS compared to endocrine-therapy alone.…”
mentioning
confidence: 99%
“…The combination of BEV plus an endocrine therapy with letrozole compared to letrozole alone in postmenopausal metastatic breast cancer patients has failed to improve progression-free survival in the LEA trial [15]. Recently, however, the first results of the phase III Cancer and Leukemia Group B (CALGB) trial 40503 have been presented.…”
Section: Introductionmentioning
confidence: 99%